Intellectual Capital, Female Manager Innovative Behavior And Catering Business Performance - Salma Abdullah; Ampauleng (Jurnal Manajemen, 2022)
The problem of the catering business is that tastes tend to be less tasty, mistakes in choosing non-quality cooking ingredients, and employees (chefs) tend not to be painstaking, so it is interesting to research by investigating the relationship of intellectual capital with the innovative behaviour of women managers and impacting on business performance through competitive advantage. From 25 catering businesses headed by women managers, we set managers and employees (cooks) as 75 respondents (purposive sampling) with data analysis using WarpPLS 7.0. We found that the better the intellectual capital, the better the innovative behaviour of female managers, and the better the catering business performance in Makassar City. We found that the better the intellectual capital, the better female managers' innovative behaviour, and the better the catering business performance in Makassar City. We also find that behaviour innovation is getting better so that this business has a competitive advantage and good business performance.